Tren Penggunaan Endorser Pria Dalam Iklan Kecantikan - Widuhung, Selvy; Sartika, Rawit (Jurnal Public Relations (J-PR), 2022)
The use of men as endorsers of women's beauty products is still a new thing in marketing methods in Indonesia. So far, beauty products have mostly used female models because they feel that they have an image that represents the product, such as beautiful, smooth-skinned, and graceful. However, with the development of time, this trend has shifted, because many well-known brands of beauty products do not hesitate to use male models as their product endorsers. Not only abroad, this trend has also begun to penetrate the country. One of them is the Beauty Brand Nature Republic, which uses the services of a South Korean boyband, EXO, to be a model for a Soothing & Moisture Aloe Vera Gel product. By using qualitative research using the Semiotics method from Roland Barthes, researchers found the fact that one of the thoughts behind the rise of well-known brands using male endorsers for their beauty products is the assumption that women want to look beautiful not only for personal satisfaction, but also to attract the attention of the opposite sex. For this reason, the use of male models who become female idols to promote a beauty product is considered to increase sales.